Voices Behind the Screen: A Narrative Inquiry into Short Video Addiction and Academic Procrastination Among Muslim Students in Yogyakarta - Sutipyo Ru'iya; Sutarman Sutarman; Yahaya Newae; Yusron Masduki (Yayasan Adra Karima Hubbi, 2026)
Background. High engagement in short video viewing among students can negatively impact academic activities, leading to increased academic procrastination. This tendency is exacerbated when students have low self-awareness. Purpose. This study aimed to analyze the effect of short video addiction on academic procrastination among high school students in Yogyakarta, with self-awareness serving as a moderating variable. Understanding this relationship is important for developing strategies to reduce academic procrastination and improve students' academic performance. Method. This quantitative study employed a cross-sectional design. Data were collected using validated psychological scales measuring short video addiction, academic procrastination, and self-awareness. The sample consisted of 309 high school students. Data analysis was conducted using factor analysis via SmartPLS 3.0. Results. The hypothesis test revealed that short video addiction positively affected academic procrastination, explaining 53.7% of the variance. Self-awareness negatively affected academic procrastination, accounting for 32.1% of the variance. Meanwhile, self-awareness was not statistically proven to moderate the effect of short video addiction on academic procrastination, because the p-values ??were 0.066 > 0.05. Conclusion. Higher short video addiction was associated with higher levels of academic procrastination, while higher self-awareness was associated with lower levels of academic procrastination. However, self-awareness does not play an effective role in moderating the effect of short video addiction on academic procrastination.